2019
DOI: 10.1097/sla.0000000000002771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breast Surgery in Primary Metastasized Breast Cancer

Abstract: The prospective phase III trial ABCSG-28 (POSYTIVE) could not demonstrate an OS benefit for surgical resection of the primary in breast cancer patients presenting with de novo stage IV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 27 publications
3
100
0
6
Order By: Relevance
“…However, not all patients can obtain a survival benefit from locoregional therapy. The ABCSG-28 trial did not indicate a survival benefit for locoregional surgery in de novo metastatic breast cancer (29). Another openlabeled randomized controlled trial in India also identified that breast operations could not prolong survival in patients with primary metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all patients can obtain a survival benefit from locoregional therapy. The ABCSG-28 trial did not indicate a survival benefit for locoregional surgery in de novo metastatic breast cancer (29). Another openlabeled randomized controlled trial in India also identified that breast operations could not prolong survival in patients with primary metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Survival data have been reported previously) [13]. Surgery did not provide an OS benefit (34.6 months vs 54.8 months, p = 0.267; HR 0.691; 95% CI 0.358-1.333) or TTPd and TTPl ( HR 0.598, p = 0.0668; HR 0.933, p = 0.882) [13]. (Figure 2a und 2b) QoL assessment as predictor for OS and TTPd…”
Section: Resultsmentioning
confidence: 81%
“…Our trial, which was halted prematurely, indicated that primary surgery does not improve OS, TTPd or TTPl in women presenting with MBC [13].This makes QoL outcomes all the more important. Our results indicate that global health status, physical functioning, social functioning, and future perspective were predictors for OS and/or TTTd.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations